Privatization : Lessons from Jordan - Mako, William P. (World Bank, Washington, DC, 2013)
While many governments in the Arab world have undertaken some privatizations since the early 1990s, many retain surprisingly large portfolios of fully, majority, or minority state-owned enterprises (SOEs). As in other parts of the world, privatization often causes concerns among citizens. Workers fear loss of employment and benefits; consumers worry about price increases; and voters mistrust government officials. Jordan's experience during 1998 - 2008, when the Government of Jordan (GOJ) privatized fourteen SOEs in telecommunications, electricity, air transport, mining and other sectors with technical assistance program financing from the U.S. Agency for International Development (USAID) demonstrates both how privatization can provide a wide range of benefits to society and how to implement a privatization program. Privatization is contentious, and it can be difficult to demonstrate the benefits. To do so, it will be useful to establish a pre-privatization baseline in terms of the enterprise performance results, employment effects, fiscal effects, investment, and competitiveness to be expected in a counter-factual case where the enterprise remains under state-ownership.